Synthesis of W-Doped TiO2 Material Ratio Using One-Step Solvothermal Method and Treatment Orientation of Volatile Organic Compounds - Chau, Hung Dung; Tuu, Tran Thi; Sy, Phung Chi; Tan, Lam Van; Tran, Thi Kim Ngan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
In TiO2 photocatalysts have been interested in the world thanks to many advantages in handling toxic compounds, with great potential for practical application at low cost. However, the electron-hole recombination rate is still high and can not be processed under visible light, which is a major limitation of this material. Modification of TiO2 by W6+ is a possible solution, however there is still little research and the optimal W6+ ratio in small amounts is still low. The material was synthesized by a one-stage solvothermal method at 200 ºC for 10 hours, without using any surfactants or post-reaction calcination with doped W molar ratios of 0.5%, 1%, and 1.5%. The result was that the TiW-1.5% catalyst sample had the highest specific surface area of 175 m2/g, higher than pure TiO2 of 160.0 m2/g. The W6+ ion successfully replaced Ti4+ in the TiO2 crystal lattice, reducing the band gap energy of the catalytic sample to 2.88 eV with the TiW-1.5% sample. For TiW-0%, the formaldehyde decomposition ability is 53.50%. Doping W into TiO2 increased catalytic efficiency, with a material sample with an optimal modified W content of 1.5% mol W having a formaldehyde decomposition efficiency of 71.98%. Research results show that W modification can improve the activity of TiO2 and increase the efficiency of volatile organic compound treatment. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).